Analysis of energetic amino acid metabolism in Acyrthosiphon pisum: a multidimensional approach to amino acid metabolism in aphids - Febvay, G. (INSA, Villeurbanne, France.); Liadouze, I; Guillaud, J; Bonnot, G (Archives of insect biochemistry and physiology, 1995)
Aphids are highly specialized insects that feed on the phloem-sap of plants, the amino acid composition of which is very unbalanced. Amino acid metabolism is thus crucial in aphids, and we describe a novel investigation method based on the use of 14C-labeled amino acids added in an artificial diet. A metabolism cage for aphids was constructed, allowing for the collection and analysis of the radioactivity incorporated into the aphid body, expired as CO2, and rejected in the honeydew and exuviae. This method was applied to the study of the metabolism of eight energetic amino acids (aspartate, glutamate, glutamine, glycine, serine, alanine, proline, and threonine) in the pea aphid, Acyrthosiphon pisum. All these amino acids except threonine were subject to substantial catabolism as measured by high 14CO2 production. The highest turnover was displayed by aspartate, with 60% of its carbons expired as CO2. For the first time in an aphid, we directly demonstrated the synthesis of three essential amino acids (threonine, isoleucine, and lysine) from carbons of common amino acids. The synthesis of these three compounds was only observed from amino acids that were previously converted into glutamate. This conversion was important for aspartate, and lower for alanine and proline. To explain the quantitative results of interconversion between amino acids, we propose a compartmentation model with the intervention of bacterial endosymbiotes for the synthesis of essential amino acids and with glutamate as the only amino acid supplied by the insect to the symbioses. Moreover, proline exhibited partial conversion into arginine, and it is suggested that proline is probably indirectly involved in excretory nitrogen metabolism